2013
DOI: 10.1097/sla.0b013e31827ee6b0
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Air Ambulance Distribution and Trauma Mortality

Abstract: For individuals residing distant from a TC, proximity to 1 airbase is associated with reduced risk of death. No additional benefit is observed when airbases are positioned close to a TC or other airbases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Several studies demonstrated that proximity and access to trauma center care are associated with improved overall survival after injury. 38,39 However, our study provides the first direct evidence to suggest that states with poor access to definitive trauma center care have more pre-hospital deaths, which contributes toward higher overall injury mortality. This effect is further magnified in rural population clusters, in line with previous work documenting the "rural risk" after injury.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies demonstrated that proximity and access to trauma center care are associated with improved overall survival after injury. 38,39 However, our study provides the first direct evidence to suggest that states with poor access to definitive trauma center care have more pre-hospital deaths, which contributes toward higher overall injury mortality. This effect is further magnified in rural population clusters, in line with previous work documenting the "rural risk" after injury.…”
Section: Discussionmentioning
confidence: 76%
“…The inclusion of EMS time and prehospital pulse rate as continuous baseline covariates may have improved the PS model as Austin in 2011 indicated that continuous variables in the model could minimize the mean squared error of the resultant estimated treatment effect, denoting that there was less difference between the true estimator and what is estimated. It is believed that prospective randomized trials are neither practical nor ethical when it comes to impact of HT on trauma mortality . However, analysis using a PS‐matched data set mimics a randomized controlled trial by balancing only known covariates …”
Section: Discussionmentioning
confidence: 99%
“…We only considered trauma centers; however the geographic distribution of other trauma system resources such as helicopter bases can also influence outcome. 30 In addition to the geospatial configuration of trauma centers, appropriate triage and utilization of these resources varies geographically and impacts outcomes.…”
Section: Discussionmentioning
confidence: 99%